Language Change and Cultural Transformation: The Impact of TikTok on Language Use Among Generation Z - Nur Aziz Abdillah; Minatur Rokhim; Ali Hasan Al Bahar; Mozzarella Najwa Mulyana Putri; Najla (Vol. 3 No. 1 (2025): Proceeding of International Conference on Cultures & Languages 2025)
This article explores the phenomenon of language change and cultural transformation triggered by the consumption and production of content on TikTok. Using a qualitative approach based on content analysis and in-depth interviews, this study identifies distinctive language patterns, such as the mixing of Indonesian and English codes, the adoption of new vocabulary from global trends, and changes in word meanings. The results show that the use of TikTok drives language shifts, where local languages tend to be marginalized in online interactions, while informal and expressive language styles become increasingly dominant. Additionally, cultural transformation is evident in the growing influence of global popular culture, which shapes the identity, entertainment preferences, and lifestyle of Generation Z in Indonesia. However, creative adaptations are also observed, where local cultural elements are packaged in global formats to attract a broader audience. These findings provide insights into the role of social media in shaping language and cultural dynamics, while also opening opportunities to utilize it as a medium for preserving local identity in the digital age.